PENGEMBANGAN PERANGKAT PEMBELAJARAN MELALUI MODEL PEMBELAJARAN BERBASIS KEARIFAN LOKAL KALIMANTAN SELATAN UNTUK MENINGKATKAN KETERAMPILAN METAKOGNITIF DAN BERPIKIR KRITIS PESERTA DIDIK KONSEP KLASIFIKASI MAKHLUK HIDUP - Munirah, Kultsum; Ramdiah, Siti; Prayitno, Budi (Florea : Jurnal Biologi dan Pembelajarannya, 2020)
One of the problems in our education world is the weakness of the learning process, which has an impact on metacognitive skills and critical thinking skills of students. One of the contributing factors is that the teacher only provides existing material without any development related to the real world of students. Thus the effort that can be made is that before carrying out the learning process the teacher as an educator must have a learning plan, which is included in the learning tool. Because in a learning device a teacher can design learning methods and materials that are considered innovative when used. One of the innovative learning methods that can build active learning conditions for students is to use a local wisdom-based learning model. The research objective was to determine the validity of learning tools through a learning model based on local wisdom of South Kalimantan to improve metacognitive skills and critical thinking of students in the classification concept of living things. This study develops products in the form of RPP, LKPD and Questions. The development method used refers to 4-D development which has 4 stages, namely define, design, develop and disseminate. The type of data used is qualitative and quantitative data. The instrument used was a validation sheet that was declared valid based on the results of the expert team's assessment. Data analysis techniques were carried out by matching the results of empirical validation from experts with predetermined validity criteria. The results of this study indicate that local wisdom-based learning tools are worth trying out, because the scores obtained from the validation results show validity with a percentage of> 67.19% which is considered valid enough and has no revised information